Abemaciclib in combination with endocrine therapy for the treatment of HR-positive/HER2-negative locally advanced/metastatic breast cancer in the UK: an observational study - Judy King; Walid Fakhouri; Rosalind Jarvis; Waleed Badreldin; Gavin Harper; Carlo Palmieri; Mark Nathan (BMC Cancer)
Abstract Background Cyclin-dependent kinase 4/6 inhibitors combined with endocrine therapy are now standard of care in the first- or second-line settings for hormone receptor positive (HR+), human epidermal growth factor 2 negative (HER2-) patients with advanced / metastatic breast cancer (ABC/MBC). Abemaciclib was first authorised in the United Kingdom (UK) in 2018 via patient access schemes before approval for routine use. This study assessed the treatment patterns and outcomes of abemaciclib in combination with endocrine therapy in a real-world setting. Methods This was an observational, multi-centre retrospective chart review of women in the UK with HR+, HER2- ABC/MBC treated with abemaciclib plus endocrine therapy during 07/2021 to 05/2022 with $$\:\ge\:$$ 3 months’ follow-up data. Data were summarised using descriptive analyses. Kaplan-Meier methods estimated time to progression (TTP) with 95% confidence intervals (CIs). Results One hundred seventy-four adult women from 9 institutions were included. Median patient age at abemaciclib initiation was 65.2 years. Best tumor response was recorded in 78.2% (n = 136) of patients; 0.7% had complete response, 27.9% had partial response, 59.6% had stable disease and 11.8% had disease progressed. Abemaciclib was associated with a 12-month TTP rate of 81.1% (first line), 68.2% (second line) and 58.2% (third line). The median TTP for patients who received abemaciclib in the first, second, and third line of treatment was: not reached, 27.7 months (95% CI: 11.7 months–not reached), and 19.3 months (95% CI: 7.7–21.9 months), respectively. Conclusions These findings support the benefit of abemaciclib in women with HR+, HER2- ABC/MBC in the real-world and complement data from MONARCH 2 and 3 clinical trials.